2023
DOI: 10.1371/journal.pone.0264469
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure of the maize weevil, Sitophilus zeamais, in southern Mexico

Abstract: The maize weevil, Sitophilus zeamais, is a ubiquitous pest of maize and other cereal crops worldwide and remains a threat to food security in subsistence communities. Few population genetic studies have been conducted on the maize weevil, but those that exist have shown that there is very little genetic differentiation between geographically dispersed populations and that it is likely the species has experienced a recent range expansion within the last few hundred years. While the previous studies found little… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…It is therefore concluded that there is no specific trend in the response, as it seems that once these beetles were exposed to the active compound, they became more active in terms of walking, climbing, and decreasing stop durations. These findings suggest that these two sister species [ 64 ] react variably in contact with the same insecticide at sublethal concentrations. They also shed light on important negative effects of chlorantraniliprole, especially in lower concentrations, that can affect the motor activity and flying capacity of S. oryzae and eventually their population ecology.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore concluded that there is no specific trend in the response, as it seems that once these beetles were exposed to the active compound, they became more active in terms of walking, climbing, and decreasing stop durations. These findings suggest that these two sister species [ 64 ] react variably in contact with the same insecticide at sublethal concentrations. They also shed light on important negative effects of chlorantraniliprole, especially in lower concentrations, that can affect the motor activity and flying capacity of S. oryzae and eventually their population ecology.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that if these techniques succeed in the field, then they will also be considered for development in other pest species. S. zeamais may be a targeted species because of its widespread geographic distribution and the threat to food security that it poses to subsistence farmers in developing nations ( Corrêa et al, 2017 ; García-Lara, García-Jaimes & Bergvinson, 2019 ; Baltzegar et al, 2023 ). However, for genetic-based technologies to be a feasible option for controlling S. zeamais , more species-specific genetic information and tools need to exist.…”
Section: Introductionmentioning
confidence: 99%